2014
DOI: 10.1364/oe.22.007865
|View full text |Cite
|
Sign up to set email alerts
|

A femtosecond pulse fiber laser at 1935 nm using a bulk-structured Bi_2Te_3 topological insulator

Abstract: We experimentally demonstrate a femtosecond mode-locked, all-fiberized laser that operates in the 2 μm region and that incorporates a saturable absorber based on a bulk-structured bismuth telluride (Bi(2)Te(3)) topological insulator (TI). Our fiberized saturable absorber was prepared by depositing a mechanically exfoliated, ~30 μm-thick Bi(2)Te(3) TI layer on a side-polished optical fiber platform. The bulk crystalline structure of the prepared Bi(2)Te(3) layer was confirmed by Raman and X-ray photoelectron sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
129
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 261 publications
(134 citation statements)
references
References 65 publications
(44 reference statements)
3
129
1
1
Order By: Relevance
“…그 중 펨토초 레벨의 극초단 펄스 레이저를 구현하기 위해서는 수 동형 모드잠금 방법을 사용하여야 하는 것으로 알려져 있다. 특히 펨토초 극초단 펄스를 생성하기 위해서는 일반적으로 반응시간이 극히 짧은 수동형 포화흡수체의 비선형 흡수 현 상을 이용하거나 편광기를 공진기 내부에 삽입하여 공진하 는 빔이 광섬유내 에서 Kerr 비선형 현상으로 인해 편광이 [15,16] Carbon Nanotube, [17] Graphene, [18][19][20][21] Topological Insulator [22] [27]…”
Section: 서 론unclassified
“…그 중 펨토초 레벨의 극초단 펄스 레이저를 구현하기 위해서는 수 동형 모드잠금 방법을 사용하여야 하는 것으로 알려져 있다. 특히 펨토초 극초단 펄스를 생성하기 위해서는 일반적으로 반응시간이 극히 짧은 수동형 포화흡수체의 비선형 흡수 현 상을 이용하거나 편광기를 공진기 내부에 삽입하여 공진하 는 빔이 광섬유내 에서 Kerr 비선형 현상으로 인해 편광이 [15,16] Carbon Nanotube, [17] Graphene, [18][19][20][21] Topological Insulator [22] [27]…”
Section: 서 론unclassified
“…In order to generate ultrashort 2 μm pulsed laser sources, approaches to passively mode-locked thulium-doped lasers have been intensively investigated by making use of different kinds of saturable absorbers (SAs), such as semiconductor saturable absorber mirrors (SESAMs) [6][7][8] , graphene or graphene oxide [9][10][11][12] , and topological insulators [13,14] . With outstanding nonlinear optical properties, such as the low threshold level of saturable absorption, ultrafast recovery time, and high damage threshold, together with the advantages of easy fabrication and broad operation range [15][16][17][18][19] , single-walled carbon nanotubes (SWCNTs) also have been applied as SAs in mode-locked lasers around 2 μm with various laser configurations in the past several years [2][3][4][20][21][22] .…”
mentioning
confidence: 99%
“…Since then, Bi 2 Te 3 in acetone and bulk Bi 2 Te 3 interaction with an evanescent wave has been reported for pulse laser generation in a mode-locked regime in a 1.5µm region [2][3][4]. Apart from that, Lin et al [5] demonstrated mechanical exfoliation of bulk Bi 2 Te 3 attached on a fiber connector for soliton compression in the same region [5].…”
mentioning
confidence: 99%